(untitled) (The Pakistan Development Review, 2010)
It is generally believed that the 7th National Finance Commission (NFC) Award and 18th Constitutional Amendment have taken a major step towards much needed fiscal decentralisation. While these two delegate more fiscal autonomy and transfers additional resources towards provinces, it seems difficult that tax decentralisation options provided in these two can practically be implemented. This assertion is based on historical tax decentralisation debate in Pakistan, which has made it a very complex issue in management of public finances. There are arguments both in favour and against tax decentralisation in Pakistan. Its proponents argue that tax decentralisation is an important principle of governance. They generally propose three advantages of fiscal decentralisation including; preference-matching, efficiency through competition, and increased accountability. In particular, a rational assignment of taxing powers helps providing each level of government, a control over its fiscal destiny by allowing it the choice in the level of spending. It helps assuring taxpayers that they are getting what they paid for and consequently may stimulate participation and improve/increase accountability. According to Bahl (1999), fiscal decentralisation assists in revenue mobilisation, innovation in economic activity, accountability of elected officials and grassroots participation in governance. Given this, it is probable that fiscal decentralisation lead towards improved efficiency in the use of resources as the residents in the sub-national governments can decide about their desired mix of public services and revenues that best suits them.